Determinan Penyerapan Tenaga Kerja: Kasus di Provinsi Banten - Raychan, Khalif; Siti Aisyah (Universitas Pasundan, 2025)
This research is motivated by the employment conditions in Banten Province which has the highest open unemployment rate among other provinces in Indonesia and in recent years has exceeded the national average. The purpose of this study is to analyze the effect of minimum wages, education level, health level, and open unemployment rate on labor absorption in Banten Province. This study is a quantitative study with secondary data obtained by the Central Statistics Agency. The method used is panel data analysis from eight districts/cities in Banten Province in 2017-2022. This study found that minimum wages have a positive impact and TPT has a negative impact on labor absorption in Banten Province. The government needs to set a competitive minimum wage and improve workforce skills through upskilling and reskilling, as well as build cooperation between educational institutions and industry to increase job availability and labor absorption.